Faktor – Faktor yang Mempengaruhi Niat Fraud Orderan pada Mitra Gojek di Kota Palembang - Sapira, Devi; Halin, Hamid; Emilda, Emilda (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
The aim of this research is to find out what factors influence the occurrence of fraudulent order intentions among Gojek partners in Palembang City. By using independent variables, namely incentives, order distribution, time limits and system levels with the dependent variable, namely intention to order fraud. This research uses a quantitative method by distributing questionnaires via Google Form to Gojek partners in Palembang City. With a total sample of 97 respondents and using a probability sampling technique, namely random sampling with analysis of research data using multiple linear regression analysis using the SPSS version 25 program. Based on the results of the partial hypothesis (t test) it shows that incentives, order distribution, time limits and system level has a positive and significant effect on order fraud intentions, where the t value > t table and the sig t value < 0.05. Based on the results of the simultaneous hypothesis test (F test), it shows that incentives, order distribution, time limits and system levels simultaneously have a positive and significant effect on order fraud intentions among Gojek partners in Palembang City.